2018
DOI: 10.1080/02699931.2018.1540403
|View full text |Cite
|
Sign up to set email alerts
|

When your heart is in your mouth: the effect of second language use on negative emotions

Abstract: Research on bilingualism and emotions has shown stronger emotional responses in the native language (L1) compared to a foreign language. We investigated the potential of purposeful second language (L2) use as a means of decreasing the experience of psychological distress. Native Swedish speakers read and answered questions about negative and neutral texts in their L1 (Swedish) and their L2 (English) and were asked to rate their level of distress before or after the questions. The texts and associated questions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 30 publications
1
23
0
Order By: Relevance
“…In summary, in this section we have reviewed evidence that in some cases using an L2 can dampen emotional arousal. In addition to the research cited above, many other studies have found decreased emotional resonance in an L2 [30,31,[40][41][42][43][32][33][34][35][36][37][38][39]. This finding is thus observed quite frequently, implying some validity, but many other studies have not replicated this finding [30,34,[44][45][46][47][48][49][50][51][52].…”
Section: Fear and Anxiety In An L2mentioning
confidence: 92%
“…In summary, in this section we have reviewed evidence that in some cases using an L2 can dampen emotional arousal. In addition to the research cited above, many other studies have found decreased emotional resonance in an L2 [30,31,[40][41][42][43][32][33][34][35][36][37][38][39]. This finding is thus observed quite frequently, implying some validity, but many other studies have not replicated this finding [30,34,[44][45][46][47][48][49][50][51][52].…”
Section: Fear and Anxiety In An L2mentioning
confidence: 92%
“…Further, the fact that the emotionality ratings decreased irrespective of reactivation language could be due to high L2 proficiency levels. The Swedish participants in the current study rated their English proficiency as high (as is typical in Swedish populations, see, for example, Bjärtå, 2019 andChampoux-Larsson, 2020), which may have attenuated the reducing effect of L2 on emotionality in the examined population. In bilinguals with lower L2 proficiency, a larger difference in reduction of emotionality between L1 and L2 reactivation may be expected.…”
Section: Discussionmentioning
confidence: 92%
“…Additionally, there is a large body of research showing that emotions are perceived less intensely in a second language (e.g., Caldwell-Harris, 2014Dylman & Bjärtå, 2018;Harris et al, 2003;Pavlenko, 2005;Puntoni et al, 2009) and it has been suggested that lower emotionality in a second language may explain why we tend to make different decisions in a second language compared to a first language (a phenomenon tokened as the Foreign Language effect, e.g., Cipolletti et al, 2016;Corey et al, 2017;Costa et al, 2014;Dylman & Champoux-Larsson, 2020;Geipel et al, 2015;Hayakawa et al, 2016;Keysar et al, 2012). Here, participants were only tested in their first language.…”
Section: Discussionmentioning
confidence: 99%